2022
DOI: 10.3389/fonc.2022.853034
|View full text |Cite
|
Sign up to set email alerts
|

Review: Neurological Complications From Therapies for Pediatric Brain Tumors

Abstract: Surgery, chemotherapy and radiation have been the mainstay of pediatric brain tumor treatment over the past decades. Recently, new treatment modalities have emerged for the management of pediatric brain tumors. These therapies range from novel radiotherapy techniques and targeted immunotherapies to checkpoint inhibitors and T cell transfer therapies. These treatments are currently investigated with the goal of improving survival and decreasing morbidity. However, compared to traditional therapies, these novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 173 publications
(181 reference statements)
0
7
0
Order By: Relevance
“…This may reflect that CNS cancer survivors have higher rates of neurocognitive difficulties, which are significantly associated with poorer academic and social outcomes. 29,33 Additionally, neurocognitive difficulties may be more prevalent in CCS with treatment-induced HL compared with CCS without HL. 30,59,60,[62][63][64] Future large and wellcontrolled studies comparing hearing acuity, as well as communication and neurocognitive outcomes both before and at more than one time point after cancer treatment, would be ideal to clarify the additional short-and long-term impact of treatment-induced HL for CCS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This may reflect that CNS cancer survivors have higher rates of neurocognitive difficulties, which are significantly associated with poorer academic and social outcomes. 29,33 Additionally, neurocognitive difficulties may be more prevalent in CCS with treatment-induced HL compared with CCS without HL. 30,59,60,[62][63][64] Future large and wellcontrolled studies comparing hearing acuity, as well as communication and neurocognitive outcomes both before and at more than one time point after cancer treatment, would be ideal to clarify the additional short-and long-term impact of treatment-induced HL for CCS.…”
Section: Discussionmentioning
confidence: 99%
“…However, more studies about children with CNS tumours reported significantly poorer performance in reading, perceived school functioning and peer interactions than studies encompassing any type of cancer. This may reflect that CNS cancer survivors have higher rates of neurocognitive difficulties, which are significantly associated with poorer academic and social outcomes 29,33 . Additionally, neurocognitive difficulties may be more prevalent in CCS with treatment‐induced HL compared with CCS without HL 30,59,60,62–64 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this number may be under reported and not reflect the true burden of this disease, because in patients with a brain tumour a cerebrovascular event may not be considered as a cause of clinical deterioration. Prompt diagnosis of cerebrovascular diseases, including stroke is needed to achieve maximal functional recovery, and quality of life (36). This is especially important for patients with GBM where life expectancy is short.…”
Section: Strengths and Limitationsmentioning
confidence: 99%